Where to establish the Advisory Centre on International Investment Dispute Resolution? - Suphanvasa Chotikajan Tang; Kraijakr Thiratayakinant (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2024)
This Perspective discusses the latest developments in UNCITRAL of the Advisory Centre on International Investment Dispute Resolution and argues that the Advisory Centre should be established with an initial set-up of headquarters and regional offices in order to effectively deliver its services given the unique nature of ISDS cases.
Keywords: 330